3.4 kV Breakdown Voltage Ga2O3 Trench Schottky Diode with Optimized Trench Corner Radius. (30th April 2020) - Huang, Xuan; Liao, Fei; Li, Ling; Liang, Xiao; Liu, Qiang; Zhang, Chaoqun; Hu, Xintong
Abstract : To improve the blocking performance of Ga2 O3 Schottky barrier diode (SBD), based on the field strength distribution at the bottom of the trench and edge effect, the impacts of structure parameter on breakdown voltage and the figure of merit (FOM) were investigated by TCAD simulation and optimization. The results indicated that the breakdown voltage raised as the corner radius of trench R and the trench length K increased in a certain range, in which K was employed to optimize the structure with a minor mesa width W. In addition, Al2 O3 was confirmed as an appropriate dielectric layer material in Ga2 O3 SBD. When the structure parameters were W = 1 μ m, R = 0.6 μ m, K = 0.8 μ m–0.9 μ m and Al2 O3 was selected as dielectric layer materials, a Ga2 O3 trench SBD with breakdown voltage of 3.4 kV and the FOM of over 1.7 GW·cm −2 was proposed.